Geogebra Applets and Gemini Artificial Intelligence in Separable Variable Differential Equations in Engineering Students of Antofagasta Chile - Funes, Jorge Olivares; Parada, Byron Droguett; Julian, Pablo Martin De; Burgos, Alexandra (Mathematics and Computer Science: Contemporary Developments Vol. 5, 2024)
This paper unifies the advantages of combining GeoGebra applets and Gemini AI to enhance mathematics learning for university students, specifically in the differential equations course at the University of Antofagasta, Chile. This combination of technological tools offers an innovative and effective approach to solving separable differential equations, providing students with a motivating learning experience. GeoGebra, a free dynamic geometry software, enables the creation of interactive applets that facilitate the visual and conceptual understanding of mathematics. In turn, Gemini AI complements GeoGebra applets by guiding students and adapting to their level of understanding and learning style. This integration not only improves comprehension compared to traditional methods but also fosters a more personalized and engaging learning experience. Various studies have demonstrated the benefits of using GeoGebra in mathematics teaching, and now, the inclusion of Gemini AI amplifies these advantages by offering a more adaptive learning experience. Together, this combination represents a significant advancement in the use of educational technologies to innovate mathematics learning in higher education.